2010
DOI: 10.1016/j.immuni.2010.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoembryonic Antigen-Related Cell Adhesion Molecule-1 Regulates Granulopoiesis by Inhibition of Granulocyte Colony-Stimulating Factor Receptor

Abstract: Summary Although carcinoembryonic antigen-related cell adhesion moclecule-1 (CEACAM1) is an activation marker for neutrophils and delays neutrophil apoptosis, the role of CEACAM1 in granulopoiesis and neutrophil dependent host immune responses has not been investigated. CEACAM1 expression correlated with granulocytic differentiation, and Ceacam1−/− mice developed neutrophilia due to loss of the Src- homology-phosphatase-1 (SHP-1) dependent inhibition of granulocyte-colony stimulating factor receptor (G-CSFR)-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 32 publications
12
67
0
Order By: Relevance
“…1). As previously reported [34][35][36] , high levels of CEACAM1 expression were detected on blood granulocytes (Ly6G þ ) and monocytes (CD115 þ ) with the anti-CEACAM1-specific monoclonal antibody (clone CC1, Fig. 1a).…”
Section: Ceacam1 Is Expressed On B-cell Subsetssupporting
confidence: 84%
“…1). As previously reported [34][35][36] , high levels of CEACAM1 expression were detected on blood granulocytes (Ly6G þ ) and monocytes (CD115 þ ) with the anti-CEACAM1-specific monoclonal antibody (clone CC1, Fig. 1a).…”
Section: Ceacam1 Is Expressed On B-cell Subsetssupporting
confidence: 84%
“…9 In comparison, CEACAM1 plays a key role in SHP-1-dependent expansion of bone marrow neutrophils via blocking granulocyte macrophage-CSF-signal transducer and activator of transcription 3 signaling. 42 A recent study has shown that CEACAM1 can also regulate TLR-4-triggered inflammasome activation via SHP-1-dependent negative regulation of Syk activation. 43 The Figure 7.…”
Section: Discussionmentioning
confidence: 99%
“…26,41 However, Wip1 may mainly regulate the relatively late stage of neutrophil development from its progenitor cells. It is somewhat consistent with the observation that Wip1 expression increases during the differentiation of GMPs into mature neutrophils, whereas HSCs express low levels of Wip1.…”
Section: Discussionmentioning
confidence: 99%